2017
DOI: 10.33549/physiolres.933804
|View full text |Cite
|
Sign up to set email alerts
|

Do Multiple Body Modifications Alter Pain Threshold?

Abstract: In recent years, epidemiological data has shown an increasing number of young people who deliberately self-injure. There have also been parallel increases in the number of people with tattoos and those who voluntarily undergo painful procedures associated with piercing, scarification, and tattooing. People with self-injury behaviors often say that they do not feel the pain. However, there is no information regarding pain perception in those that visit tattoo parlors and piercing studios compared to those who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In our previous study we have shown that individuals with body modifications as well as without body modifications had higher thermal pain thresholds during public demonstration of painful techniques compared to thresholds measured at control neutral conditions. These observations lead us to conclude that in emotionally charged environment, pain threshold in our participants was top-down modulated via affective and cognitive processes (Yamamotová et al 2017).…”
Section: Pain Pleasure and Expectationsupporting
confidence: 54%
“…In our previous study we have shown that individuals with body modifications as well as without body modifications had higher thermal pain thresholds during public demonstration of painful techniques compared to thresholds measured at control neutral conditions. These observations lead us to conclude that in emotionally charged environment, pain threshold in our participants was top-down modulated via affective and cognitive processes (Yamamotová et al 2017).…”
Section: Pain Pleasure and Expectationsupporting
confidence: 54%
“…The tactile threshold was tested by the von Frey method (touch-test sensory evaluators, North Coast Medical). The thermal pain threshold was measured with a portable thermal stimulator of Algic stimuli (Yamamotová et al, 2017 ), a uniquely modified device that creates thermal stimulations with steadily increasing temperature (20–70°C), until a participant indicates, by pressing the left button of a computer mouse, their first perception of the relevant sensation and then the first perception of pain (Summers et al, 2004 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is evident that hormones influence perception of pain: oestrogens mitigate pain with concentration-dependent mechanisms, whereas testosterone reduces the sensitivity to chronic pain [280]. Pain responses seem to change during life depending on hormonal variability: at puberty, the perception of pain increases in women, while sex differences in chronic pain rates disappear in menopause [281]. The gonadal hormones affect the incidence of pain, as it was observed in transsexuals who received cross sex hormones to develop and maintain somatic characteristics of the opposite sex [282].…”
Section: Sex Disparity In Pain Threshold and Feelingsmentioning
confidence: 99%